2012
DOI: 10.1371/journal.pone.0052245
|View full text |Cite
|
Sign up to set email alerts
|

Using Phylogenetic and Coalescent Methods to Understand the Species Diversity in the Cladia aggregata Complex (Ascomycota, Lecanorales)

Abstract: The Cladia aggregata complex is one of the phenotypically most variable groups in lichenized fungi, making species determination difficult and resulting in different classifications accepting between one to eight species. Multi-locus DNA sequence data provide an avenue to test species delimitation scenarios using genealogical and coalescent methods, employing gene and species trees. Here we tested species delimitation in the complex using molecular data of four loci (nuITS and IGS rDNA, protein-coding GAPDH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 107 publications
5
48
1
Order By: Relevance
“…[MW3]All but one of the studied phenotypic characters that were previously used for species circumscription in the C. furcata complex have here been shown to be highly homoplasious ( Table 2). This is consistent with previous studies that had also found high homoplasy levels for phenotypic characters within Cladoniaceae (Pino-Bodas et al 2011;Parnmen et al 2012). For example, the presence of scyphi (Pino-Bodas et al 2011), or the presence of soredia (Stenroos et al 2002) were shown to be highly homoplasious in other groups of Cladoniaceae.…”
Section: Discussionsupporting
confidence: 92%
“…[MW3]All but one of the studied phenotypic characters that were previously used for species circumscription in the C. furcata complex have here been shown to be highly homoplasious ( Table 2). This is consistent with previous studies that had also found high homoplasy levels for phenotypic characters within Cladoniaceae (Pino-Bodas et al 2011;Parnmen et al 2012). For example, the presence of scyphi (Pino-Bodas et al 2011), or the presence of soredia (Stenroos et al 2002) were shown to be highly homoplasious in other groups of Cladoniaceae.…”
Section: Discussionsupporting
confidence: 92%
“…A likelihood ratio test (LRT) was used to evaluate whether the null model was to be rejected or not. If the GMYC model fits the data significantly better than the null model, the threshold T allows estimation of the number of species present in the dataset (Parnmen et al 2012). The GMYC method requires an ultrametric tree without identical sequences to avoid zero length terminal branches that hamper the likelihood estimation (Fujisawa and Barraclough 2013).…”
Section: Species Delimitationmentioning
confidence: 99%
“…This has been shown in other cases as well (see e.g. Parmelia barrenoae, ; Physconia thorstenii, Divakar et al (2007); Caloplaca citrina group Vondrák et al (2009); Melanelixia californica, ; Parmelia mayi, Molina et al (2011a); Cladia aggregata group, Parnmen et al (2012); Parmotrema perforatum group, Widhelm et al in press) and demonstrates the importance of careful re-analysis of morphological and chemical characters in order to phenotypically circumscribe species. Further, the species-level lineages uncovered in this widely distributed isidiate taxon showed biogeographic structure in what was previously believed to be a pantropical species.…”
Section: Resultsmentioning
confidence: 54%
“…Further, the species-level lineages uncovered in this widely distributed isidiate taxon showed biogeographic structure in what was previously believed to be a pantropical species. Although geographical structure of species detection using molecular data has recently been shown to be a common phenomenon in lichenized fungi (Argüello et al 2007;Divakar et al 2010a;Otalara et al 2010;Amo de Paz et al 2012;Parnmen et al 2012;Moncada et al 2014;Leaviit et al 2015b;Alors et al 2016); caution must be taken to generalizing for all isidate lichen taxa (Leavitt et al 2013a;Roca-Valiente et al 2013;Divakar et al 2016). Etymology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation